Teachers' and Students' Perceptions of the Three-Phase Technique in Reading Instruction: A Qualitative Study - Ferdiyanto, Feri (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This qualitative study explores teachers' and students' perceptions of the Three-Phase Technique (TPT) in reading instruction, a method designed to enhance reading comprehension through three distinct stages: pre-reading, while-reading, and post-reading. Data were collected through semi-structured interviews with 5 teachers and 10 students in senior high school, classroom observations, and document analysis. The findings reveal that both teachers and students recognized the benefits of TPT in improving reading comprehension, particularly in activating prior knowledge, maintaining focus during reading, and promoting deeper reflection post-reading. However, time constraints and the need for differentiation emerged as key challenges in its implementation. Teachers noted that adjusting the technique to meet the diverse needs of students was essential for maximizing its effectiveness. The study also highlighted the importance of metacognitive awareness, with both teachers and students emphasizing how the reflective nature of TPT encouraged students to become more self-aware of their reading strategies. These findings suggest that while TPT is a valuable tool for enhancing reading comprehension, its implementation requires thoughtful adaptation to address the unique challenges within each classroom setting.